Synthesis and Characterization of Highly Crystalline Vertically Aligned WSe2 Nanosheets - Ayrton Sierra-Castillo; Emile Haye; Selene Acosta; Carla Bittencourt; J.-F. Colomer (Applied Sciences, 2020)
Here, we report on the synthesis of tungsten diselenide (WSe2) nanosheets using an atmospheric pressure chemical vapor deposition technique via the rapid selenization of thin tungsten films. The morphology and the structure, as well as the optical properties, of the so-produced material have been studied using electron microscopies, X-ray photoelectron spectroscopy, photoluminescence, UV−visible and Raman spectroscopies, and X-ray diffraction. These studies confirmed the high crystallinity, quality, purity, and orientation of the WSe2 nanosheets, in addition to the unexpected presence of mixed phases, instead of only the most thermodynamically stable 2H phase. The synthesized material might be useful for applications such as gas sensing or for hydrogen evolution reaction catalysis.